2018
DOI: 10.1111/ane.12967
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of myasthenia gravis in Chilean population

Abstract: This study reduces the gap in information about MG in South America. The prevalence of MG in Chile is within the range described worldwide. We did not see an increase in male frequency in the older age of onset group and thymoma was more frequent in the fifth and sixth decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(48 reference statements)
0
7
1
3
Order By: Relevance
“…We report the PR of symptomatic MG of 22.65 per 100,000. It is higher than that in previous studies using pyridostigmine databases, with PR ranging from 8.36 to 13.1 per 100,000 [6, 7, 14, 25, 26], but within the range of those reported in the epidemiological MG studies using other case collection methods (between 7.7 and 32.0 per 100,000) [5, 11, 15, 17, 18, 23, 27-30]. It may reflect a trend towards higher PRs, noted in most recent studies.…”
Section: Discussioncontrasting
confidence: 62%
“…We report the PR of symptomatic MG of 22.65 per 100,000. It is higher than that in previous studies using pyridostigmine databases, with PR ranging from 8.36 to 13.1 per 100,000 [6, 7, 14, 25, 26], but within the range of those reported in the epidemiological MG studies using other case collection methods (between 7.7 and 32.0 per 100,000) [5, 11, 15, 17, 18, 23, 27-30]. It may reflect a trend towards higher PRs, noted in most recent studies.…”
Section: Discussioncontrasting
confidence: 62%
“…Worldwide prevalence is 1.5–17.9 per 100,000 and incidence 0.3–3 per 100,000 1,2 . The estimated prevalence of MG in Chile is 8.39 per 100,000 3 . Clinically, MG is characterized by weakness and excessive muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous nationwide studies reported percentage of patients ever treated with CS or other IS ranging from 42% to 90% for CS and 28.1%–43% for other IS, with the highest rates reported in voluntary, patient‐submitted database 6‐10 . In our previous hospital‐based registry study, 11 the proportion of patients ever treated with CS was 57.2%, and 41.5% had no history of CS use.…”
Section: Discussionmentioning
confidence: 76%